2021
DOI: 10.1101/2021.08.24.21262522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Procalcitonin to Predict Severity of Acute Cholangitis and Need for Urgent Biliary Decompression: Systematic Scoping Review

Abstract: Background: Serum Procalcitonin (PCT) has been reported as a potential biomarker to predict the severity of acute cholangitis (AC) or the need for urgent biliary decompression. This study aimed to identify and summarize the existing research about the serum PCT and the severity of AC, and to find gaps where future studies can be targeted towards. Methods: Following the PRISMA Extension for Scoping Reviews, MEDLINE, EMBASE, and Google Scholar were searched for all peer-reviewed articles with relevant keywords … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Six studies were included in this study. We found that the sample size was lower in all studies than in our study.In all studies, procalcitonin level was found to be higher in severe acute cholangitis patients compared to mild and moderate acute cholangitis patients (23). In our study, similar to the above studies, procalcitonin level was found to be highest in severe acute cholangitis patients, then in moderate acute cholangitis patients and lowest in mild cholangitis patients.…”
Section: Discussionsupporting
confidence: 89%
“…Six studies were included in this study. We found that the sample size was lower in all studies than in our study.In all studies, procalcitonin level was found to be higher in severe acute cholangitis patients compared to mild and moderate acute cholangitis patients (23). In our study, similar to the above studies, procalcitonin level was found to be highest in severe acute cholangitis patients, then in moderate acute cholangitis patients and lowest in mild cholangitis patients.…”
Section: Discussionsupporting
confidence: 89%